Peran Pendidikan Agama Islam dalam Memperkuat Kesadaran Lingkungan (Environmental Awareness) pada Peserta Didik SMAN 1 Batur, Kabupaten Banjarnegara - Alfana Salsabila; Fatturrokhman Fatturrokhman; Fatiatun Fatiatun (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
Islamic religious education to strengthen environmental awareness at SMA N 1 Batur has succeeded in instilling environmental awareness in students through real activities and teaching on religious values. Students are active in protecting the school environment and understand the importance of protecting nature. The level of environmental awareness of students at SMA N 1 Batur is quite good. It is evident through the activeness of students in real activities such as class pickets, clean Fridays, and school cleaning activity implementation programs, students not only maintain school cleanliness but also understand the importance of a clean environment for the learning process. The data collection method is carried out through observation, interviews, and documentation. Meanwhile, the data analysis used used descriptive techniques with qualitative data types.